2016
DOI: 10.1111/jog.12956
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognosis of bone metastasis from cervical cancer (KCOG‐G1202s)

Abstract: Multidisciplinary treatment might improve the prognosis of patients with bone metastasis who do not have extra-osseous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…In patients with CC who have distant and multiple recurrent disease, the primary aim of treatment is mostly not-curative intent but palliative (19) . However, in a study presented by Makino et al (20) of 75 patients with uterine CC and bone recurrence, the overall survival (OS) of 16 patients who received chemotherapy and CCRT after RT was 18 months and 2 months, respectively, compared with 25 patients receiving palliative treatment (p<0.05). In our case series, complete clinical response was obtained with salvage treatment in two patients in the presence of isolated recurrence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In patients with CC who have distant and multiple recurrent disease, the primary aim of treatment is mostly not-curative intent but palliative (19) . However, in a study presented by Makino et al (20) of 75 patients with uterine CC and bone recurrence, the overall survival (OS) of 16 patients who received chemotherapy and CCRT after RT was 18 months and 2 months, respectively, compared with 25 patients receiving palliative treatment (p<0.05). In our case series, complete clinical response was obtained with salvage treatment in two patients in the presence of isolated recurrence.…”
Section: Discussionmentioning
confidence: 95%
“…Ida et al (29) were able to control the disease by surgical resection in a solitary femur recurrence that developed 22 months after the first treatment. However, Makino et al (20) reported that in two patients with solitary bone recurrence, complete resection could not be achieved. We had no patients who could be managed surgically in this series.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The use of SPECT/CT is therefore likely to result in an earlier and better allocation of appropriate management for these patients. In addition, the reduction in the number of patients with equivocal diagnoses is likely to result in the avoidance of costly additional imaging or invasive investigations.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,6,9 The most frequent site of bone metastasis was the vertebral column (46.7%Y59.0%; 4.5% cervical, 15.1%Y18.1% thoracic, and 30.7%Y36.4% lumbar). 2,4,10 Extraskeletal metastases were reported in 49.5% to 92.6% of patients, and multiple bone metastases in 50.0% to 61.1%. 4,5 The incidence of VM was 2.1%, and the mean age at diagnosis was 55.8 T 10.0 years in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Extraskeletal metastasis, a short DFS (G12 months), and multiple bone metastases all (negatively) affected survival after the detection of bone metastasis. 5,9,10 We created a case-control group matched to VM patients in terms of histological subtype and stage. We found that, on univariate regression analysis, the hemoglobin level (G12 g/dL) was a risk factor for VM development.…”
Section: Discussionmentioning
confidence: 99%